Innovative Methods for Underground Parking in Central Cities - Guanglei Liu; Qi Wang; Zengzhu Kang; Jianguo Liu (Deep Foundations Institute, 2017)
"Due to the increase of automotive vehicles, available parking spaces become a new type of limited resource in central cities of China, especially in those old districts without visionary urban planning. Additional mechanical parking in underground space is an efficient solution to provide parking spaces under the situation where the urban space is constrained. Shichahai district is an old protected zone in Beijing which is close to the Forbidden City and there are many Hutong (alleyway) and Quadrangles (courtyard house). No spaces are available for car parking on the ground and all vehicles are parking in Hutong without order currently. The local government plan to do renovation work for this district and improve the residential environment. Several innovative solutions are studied including parking in deep shafts, parking under existing buildings by under-pinned method, parking under buildings by covered excavation method, parking under roads built together with utility tunnel etc. 5000 difference types underground parking spaces are planned to be constructed in the following three years. Project examples are also introduced in this paper. INTRODUCTIONCar parking resources are very limited in central cities, especially in old districts without planning for increasing automotive vehicle volume. Traffic get worse when cars park on the side of the roads or move slowly to find parking spaces. Investigation shows the normal (parking space/ automotive vehicle volume) ratio is about 1.2 in most big cities such as New York, Tokyo and Hong Kong, while this ratio is only 0.5 in Beijing. One solution is to move cars out of central cities. But there are still huge parking requirements for the citizens living in central cities. Shichahai district is an historic protected zone in Beijing which is close to the Forbidden City and there are many Hutong and Quadrangles (refer to Figure 1 for project location). No spaces are available for car parking on ground and all vehicles are parked in Hutong without order currently. The local government had a plan to do renovation work of this district and improve the residence environment. 5000 different types of underground parking spaces are planned to be constructed in the following three years. One project designed and to be constructed by Zhongyan Technology will be introduced in this paper. Other innovative solutions will be introduced briefly as well."